KURANG/LEBIH BAYAR TRANSFER ANTAR PEMERINTAH PADA SEKTOR MINERAL DAN BATUBARA - Teguh, Yosua Martin (Universitas Pendidikan Indonesia, 2019)
In implementing fiscal decentralization in Indonesia there is a phenomenon of under/overpayment of revenue sharing of natural resources from the Central Government to Regional and Local Governments that lead to debt and receivables among government agencies. This study aims to answer why and how this phenomenon occurs and its effects. The strategy of this research is a case study with a qualitative approach to financial data, regulation, and interviews with related sources. The results of the study show that less/overpayment of revenue sharing of mineral and coal is caused by poor planning, policy changes, invalid information, commodity prices, exchange rates and receivables of related non-tax revenues. This research is expected to provide an overview of the causes, conditions and impacts of under/overpayment of revenue sharing of mineral and coal phenomena so that it can reduce the potential for under/overpayment of related revenue sharing and increase transparency among governments.